1) а) (3х+9)-(ху+3у)=3(х+3)-у(х+3)=(3-у)(Х+3)
б) (2х^2+4)-(2x^4+x^6)=2(x^2+2)-x^4(2+x^2)=(2-x^4)(x^2+2)
2) 2xy-4y-x^3-2x=2y(x-2) -x(x^2+2)=2*2(2-2)-2(2^2+2)=0-12=-12
1)сразу решение 3xy(1+3-1-1)=3xy*2=6xy
2)2x^2(1+4-x^2-x^4)=2x^2*5-x^2-x^4=10x^2-x^2-x^4
2-задание
2xy(1-2-x^2-1)=2xy(-2-x^2)=2*2*2(-2-2*2)=8*-6=-48
1) а) (3х+9)-(ху+3у)=3(х+3)-у(х+3)=(3-у)(Х+3)
б) (2х^2+4)-(2x^4+x^6)=2(x^2+2)-x^4(2+x^2)=(2-x^4)(x^2+2)
2) 2xy-4y-x^3-2x=2y(x-2) -x(x^2+2)=2*2(2-2)-2(2^2+2)=0-12=-12
1)сразу решение 3xy(1+3-1-1)=3xy*2=6xy
2)2x^2(1+4-x^2-x^4)=2x^2*5-x^2-x^4=10x^2-x^2-x^4
2-задание
2xy(1-2-x^2-1)=2xy(-2-x^2)=2*2*2(-2-2*2)=8*-6=-48